2018
DOI: 10.11114/jets.v6i4.3085
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Aerobic and Anaerobic Training Programs Applied to Elite Wrestlers on Body Mass Index (BMI) and Blood Lipids

Abstract: The purpose of this study is to analyse the effects of aerobic and anaerobic training programs applied to elite wrestlers on body mass index (BMI) and blood lipids. 20 elite wrestlers, whose average age is (experimental group; 15.20±4.61, n=10), control group; 15.90±2.08, n=10), participated in the study and they were randomly divided into two groups. Strength and endurance training programme based on “one day aerobic, one day anaerobic” principles was applied to the experimental group six days a week for eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 14 publications
1
11
0
2
Order By: Relevance
“…Al- Abdilh and Savas (2017) reported that the Body Mass Index variable was statistically different from the results of the different type of endurance training measurements applied to young basketball players. Demirel et al (2017) found that there was no statistical difference between body mass index values of experimental and control groups in their study which consists of elite wrestlers for examining the effect of aerobic and anaerobic training program on body composition. Gokhan et al (2011) found that there was no significant difference between preliminary test values (25.2±3.3 kg/m2) and final test values (24.3±2.8 kg/m2).…”
Section: Discussionmentioning
confidence: 89%
“…Al- Abdilh and Savas (2017) reported that the Body Mass Index variable was statistically different from the results of the different type of endurance training measurements applied to young basketball players. Demirel et al (2017) found that there was no statistical difference between body mass index values of experimental and control groups in their study which consists of elite wrestlers for examining the effect of aerobic and anaerobic training program on body composition. Gokhan et al (2011) found that there was no significant difference between preliminary test values (25.2±3.3 kg/m2) and final test values (24.3±2.8 kg/m2).…”
Section: Discussionmentioning
confidence: 89%
“…Physical activity and exercise habit contribute to prevent obesity, cardiovascular diseases, diabetes and some other chronic diseases and to lead a healthy lifestyle. Exercise and physical activity are at the top of the treatment options list to prevent hyperlipidemia, one of the significant risk factors for cardiovascular diseases (Demirel et al, 2018). When literature was reviewed about effects of exercise on plasma lipids, lipoproteins, blood pressure and heart rates, results were indicated that moderate and low intensity exercıse, ıf ıts performed adequate time period decrease in body weight and body fat ratio, additionally decrease serum TC level.…”
Section: Discussionmentioning
confidence: 99%
“…Delextrat et al (2016) in a study, found maximum aerobic fitness (3.6%), physical power self-perception (16.3%) and muscle development (18.6%), more autonomy (8.0%) and significant positive changes in life goal (4.4) identified. Physical activity and exercise contribute to prevent cardiovascular and chronic diseases, obesity, diabetes, and to lead a healthy lifestyle (Demirel et al, 2018). It has been identified that regular middle exercise reduces total blood cholesterol, serum triglycerides and low density lipoprotein cholesterol (LDL-C) and increases high-density lipoprotein cholesterol (HDL-C), (İmamoğlu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%